Hubungan Antara Red Blood Cell Distribution Width dengan Nilai Estimated Glomerular Filtration Rate Pasien Penyakit Ginjal Kronik di RSUD ODSK Provinsi Sulawesi Utara - Juni Sarah Devi Sinambela; Murniati Tiho; Diana Shintawati Purwanto (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Chronic kidney disease (CKD) is a global health problem with continuously increasing prevalence and mortality. This condition is characterized by a progressive and irreversible decline in kidney function, which is clinically assessed using the estimated glomerular filtration rate (eGFR) as one of the main parameters for staging and monitoring disease progression. Red blood cell distribution width (RDW) is a hematological parameter that reflects the degree of variation in erythrocyte size. In patients with CKD, elevated RDW levels are often associated with oxidative stress and chronic inflammation, which may accelerate kidney damage and increase mortality risk. To analyze the correlation between RDW and eGFR values in patients with chronic kidney disease at ODSK Hospital, North Sulawesi Province. This study used an analytical observational design with a cross‑sectional approach. It was conducted retrospectively using secondary data from the medical records of CKD patients at ODSK Hospital, North Sulawesi Province, from February 2024 to August 2025. This study used a total sampling method with 189 CKD patients who met the inclusion and exclusion criteria.  Based on Spearman-rank correlation analysis, the p‑value obtained was 0.129 (>0.05). There was no significant relationship between RDW and eGFR values in CKD patients at ODSK Hospital, North Sulawesi.Province.